2022
DOI: 10.3390/vaccines10101706
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Antibody Response in Egyptian Healthcare Workers Vaccinated with ChAdOx1 nCoV-19 Vaccine during Delta and Omicron Variants Pandemic: A Prospective Study

Abstract: Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a constantly evolving virus, resulting in an increased burden on the existing COVID-19 vaccines. Healthcare workers (HCWs) are the first line of defense against the coronavirus disease 2019 (COVID-19) pandemic and have been prioritized among the risk categories receiving the COVID-19 vaccine. This work aimed to investigate the maintenance of antibody response of the Oxford–AstraZeneca vaccine (ChAdOx1/nCoV-19). Methods: Anti-spike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 63 publications
3
7
0
Order By: Relevance
“…Nearly two-thirds (64.8%) of the seronegative healthcare workers (HCWs) showed seroconversion rates of 81.8% and 93.3% after the first and second vaccination doses, respectively. 12 In consistent with Madhi et al 22 study in South Africa, ChAdOx1 nCoV-19 COVID-19 vaccine efficacy against B.1.351 variant was 10.4% (95% CI, −76.8 to 54.8). A two-dose regimen of the ChAdOx1 nCoV-19 vaccine did not show protection against mild-to-moderate COVID-19 due to the B.1.351 variant.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…Nearly two-thirds (64.8%) of the seronegative healthcare workers (HCWs) showed seroconversion rates of 81.8% and 93.3% after the first and second vaccination doses, respectively. 12 In consistent with Madhi et al 22 study in South Africa, ChAdOx1 nCoV-19 COVID-19 vaccine efficacy against B.1.351 variant was 10.4% (95% CI, −76.8 to 54.8). A two-dose regimen of the ChAdOx1 nCoV-19 vaccine did not show protection against mild-to-moderate COVID-19 due to the B.1.351 variant.…”
Section: Resultssupporting
confidence: 76%
“…One person with HIV died (unlikely related). As per Hammad et al, 12 safety report demonstrated that the most common adverse reactions were pain and malaise. No serious adverse event was reported.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations